2019
DOI: 10.1002/ceas.12123
|View full text |Cite
|
Sign up to set email alerts
|

A 15‐Year Content Analysis of Three Qualitative Research Traditions

Abstract: The authors conducted a qualitative content analysis on the consistency, rigor, and methodological identity of 83 phenomenological (n = 44), grounded theory (n = 25), and consensual qualitative research (n = 14) articles published between 2002 and 2016. The results indicate a distinct pattern of qualitative research practices in professional counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…In qualitative designs, reviews of counseling research publications (generally, not only in teaching) concluded researchers did not consistently report the paradigm, tradition, or trustworthiness strategies employed (Flynn et al, 2019;Hays et al, 2016). Further, Kline (2008) emphasized that coherence across the qualitative design is important -meaning, when a manuscript depicting qualitative research is under review, reviewers are looking for attention to congruence among the chosen tradition and research questions; consistent use of paradigm throughout the procedure and analysis; and reflection of the tradition's data analysis procedures.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In qualitative designs, reviews of counseling research publications (generally, not only in teaching) concluded researchers did not consistently report the paradigm, tradition, or trustworthiness strategies employed (Flynn et al, 2019;Hays et al, 2016). Further, Kline (2008) emphasized that coherence across the qualitative design is important -meaning, when a manuscript depicting qualitative research is under review, reviewers are looking for attention to congruence among the chosen tradition and research questions; consistent use of paradigm throughout the procedure and analysis; and reflection of the tradition's data analysis procedures.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…While some address this limitation by reporting survey development protocols (Burton & Furr, 2014), others have chosen to simply list it as a limitation (Giordano et al, 2019). Finally, given the push in qualitative research for multiple data sources (see Flynn et al, 2019;Hays et al, 2016), authors who only report one data source are challenged to address this decision in their limitations.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Unfortunately, in JCD publications, researchers found that 82.4% of qualitative studies (56 articles) did not report their paradigm or philosophical underpinning (Hays et al, 2016). Additionally, Flynn et al (2019) reported that although the qualitative articles in their review of Counselor Education and Supervision were readable without the discussion of ontology, epistemology, and theory, there is concern that omitting these elements is counterproductive to the foundation of qualitative data analysis in which the researchers' lens of interpretation matters (Hays & Singh, 2012).…”
Section: Critiques and Recommendationsmentioning
confidence: 99%
“…Counseling researchers may not be using lived experience research methods in their greatest capacity. That is, although counseling researchers have relied significantly on qualitative methods to explore topics of diversity (Flynn et al, 2019) or underserved populations' experiences, very few have used the designs for topics of effectiveness of counseling or counseling outcomes (Hays et al, 2016). However, experts in qualitative research approaches endorse the use of these methods for effectiveness studies.…”
Section: Critiques and Recommendationsmentioning
confidence: 99%
“…Conceptual work covered authorship practices of counselor educators (Swank, Houseknecht, & Puig, 2019); competencies with respect to integrated care (Asempapa, 2019); preparation and rationale for interprofessional work and training in the curricula (K. F. Johnson, 2019); research practice partnerships across professions (Hays et al, 2019); integration of evidence-based practices in school counseling using a three-step model promoting practitioner partnerships to promote use of evidence-based practices in fieldwork (Martin et al, 2019); and relationally oriented research agendas integrating evidence-based relationship factors into counselor training and practice, and describing specific counselor behaviors to support practice and research (Parrow et al, 2019). Qualitative studies included experiences with grant funding (Delaney & Gibson, 2019); Latina student experiences, perceptions, and beliefs regarding teaching experiences (Vela et al, 2019); new counselor educator scholarly productivity (Borders et al, 2019); patterns of qualitative research in professional counseling over the last 15 years (Flynn et al, 2019); and the development and application of a collaboration between counseling students and master's students in a writing program (Reese, 2019).…”
Section: Stakeholder Experiencesmentioning
confidence: 99%